Paclitaxel-induced cognitive impairment: mechanistic insights - Alhowail, Ahmad Hamad (Frontiers in Pharmacology, 2025)
Paclitaxel, a cornerstone taxane for solid-tumor chemotherapy, frequently precipitates long-lasting cognitive deficits, which are collectively termed chemotherapy-related cognitive impairment and often referred to as chemobrain or chemofog. Although the precise mechanisms are still being fully elucidated, a growing body of evidence from preclinical and clinical studies points to several key pathways and cellular targets. Evidence suggests that paclitaxel exerts potential neurotoxic effects through various mechanisms of action that stabilize microtubules and reduce their dynamicity, promoting mitotic halt and cell death. In this review, the major mechanisms and effects of paclitaxel are concisely summarized; these include neuroinflammation, oxidative stress, impaired neurogenesis and synaptic plasticity, neuronal apoptosis, hormonal imbalance, calcium dysregulation, altered white matter integrity, and mitochondrial dysfunction. By synthesizing published mechanistic data, this review highlights emerging molecular targets and experimental therapeutics to help prevent and mitigate paclitaxel-induced cognitive impairment.